Indication Of Hydrothermal Alteration Based On Petrography Of Granit Garba (KGR), Tanjung Beringin Village, Muaradua District, South Sumatera - Salsyabillah Nurul Aini; Endang Wiwik Dyah Hastuti (Jurnal Geomine, 2022)
The research was conducted in Tanjung Beringin Village, Muaradua District, South OKU Regency, South Sumatra. The location of this research is geologically located in the basement of the South Sumatra Basin which composes the Garba Mountains, namely Granit Garba. Granit Garba is an intrusion rock with the youngest age among the basement rocks forming the South Sumatra Basin. The lithology that composes this formation is a granitoid rock with interesting constituent mineral characteristics and there are indications of hydrothermal alteration processes that affect rock formation. The characteristics and hydrothermal alteration of these granitoid rocks can be identified using petrographic analysis of rock thin sections. Based on the petrographic analysis, it is interpreted that there are two groups of granitoids that make up Granit Garba. The two groups of granitoids are quartz monzonite and granodiorite. The difference between the two types of rock lies in the composition of the main mineral constituents. Quartz monzonite is a rock with minimal quartz composition and relatively the same percentage of plagioclase and alkali feldspar. Meanwhile, granodiorite has more quartz composition than quartz monzonite with relatively more plagioclase minerals than alkali feldspar minerals. The appearance of the thin section in the petrographic analysis of the rock also shows the influence of hydrothermal alteration as evidenced by the presence of secondary minerals. These secondary minerals form associations that occur in the phylic and propylitic zones. The phyllic zone is indicated by the presence of sericite, chlorite, and opaque minerals in the form of pyrite, while the propylitic zone has an assemblage of epidote, chlorite, and calcite minerals.